2004
DOI: 10.1080/01926230490260871
|View full text |Cite
|
Sign up to set email alerts
|

Hexachlorobenzene-Induced Incisor Degeneration in Sprague—Dawley Rats

Abstract: Hexachlorobenzene (HCB) was administered to female Sprague-Dawley rats in a 13-week toxicity study conducted for the National Toxicology Program (NTP). Groups of 10 rats were treated by gavage with 0.0, 0.03, 0.1, 0.3, 1.0, 3.0, 10, or 25 mg/kg HCB in corn oil 5 days/week for 13 weeks. Dose-dependent, region-specific, maxillary incisor degeneration was observed in animals given HCB at doses of 1.0 mg/kg/day and higher. Treatment with 1.0 mg/kg/day resulted in focal mesenchymal cell vacuolation and focal osteod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
(40 reference statements)
2
10
0
Order By: Relevance
“…It is interesting that the histological abnormality in the klotho −/− incisor is restricted to its labial region. A similar change in the klotho −/− mice has been reported in the rat incisor suffering from HHM (hypercalcemia of malignancy; Kato et al, 2003) or treated with hexachlorobenzen (Long et al, 2004). On the other hand, Savage et al (2006) reported dentin malformations restricted to the lingual side in the mandibular incisor of p20C/EBPbeta transgenic mice.…”
Section: Discussionsupporting
confidence: 69%
“…It is interesting that the histological abnormality in the klotho −/− incisor is restricted to its labial region. A similar change in the klotho −/− mice has been reported in the rat incisor suffering from HHM (hypercalcemia of malignancy; Kato et al, 2003) or treated with hexachlorobenzen (Long et al, 2004). On the other hand, Savage et al (2006) reported dentin malformations restricted to the lingual side in the mandibular incisor of p20C/EBPbeta transgenic mice.…”
Section: Discussionsupporting
confidence: 69%
“…On day 7, the lesions moved further toward the columnar odontoblastic area, and formed fully bloomed dentin niche with the histopathological character of sharply demarcated recessed areas of dentin as defined in previous reports [12][13][14][15][16][17][18][19] . Based on this morphological sequence from the onset of cell damage to dentin niche formation and the fact that many different types of cytotoxic agents with different modes of action can consistently induce dentin niche, the lesion is considered to be the repair response of odontoblasts to cell damage [12][13][14][15][16][17][18][19] . In addition, previous autoradiographic investigations have shown that cuboidal odontoblastic cells are derived from surviving odontoblasts and hypertrophic pulpal cells, and they are considered to be a signature of regeneration of the odontoblastic layer 14,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one of the odontoblastic lesions observed in this model was identical to dentin niche, which is known to consistently develop after administration of a number of cytotoxic agents with different modes of action. Dentin niche is considered to be an odontoblastic repair response to cell damage, because of the consistency and the outcomes of time course observations of its development [12][13][14][15][16][17][18][19] . PTHrP and/or PTHR1 are known to be expressed in emerging cells during the repair processes in bone, cartilage, and skin [20][21][22][23][24] , as well as in cells contributing to normal dentinogenesis [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Also in healthy mice, VEGF signaling inhibition resulted in a reduction in the number of tracheal mucosal (Karim 1990;Satoh et al 2001) Colchicine Ameloblast degeneration, inhibition of enamel-matrix secretion (Nishikawa 2002) Dioxin Low columnar to cuboidal odontoblasts, odontoblast cell death; arrest of dentin formation; squamous metaplasia and proliferation of the enamel organ with apoptosis; pulp cell death; defects of dentin and enamel mineralization (Alaluusua and Lukinmaa 2006;Kiukkonen et al 2002) 5-Fluorouracil Disorganization of odontoblasts, focal dentin defects (Satoh et al 2001). Hexachlorobenzene Odontoblast degeneration, dentin recesses, irregular dentin matrix organization and cellular inclusions; pulp mesenchymal cell formation, osteodentin formation within the pulp (Long, Herbert, and Nyska 2004).…”
Section: Discussionmentioning
confidence: 99%